EFFECT OF DIFFERENT FEEDING LEVELS ON PRODUCTIVE PERFORMANCE AND ECONOMIC FEASIBILITY OF PEKIN DUCKS IN KURDISTAN REGION OF IRAQ - Azad Sh. S. Al-Dabbagh; Sardar. Y. T. Al- Sardary (The Iraqi Journal of Agricultural science)
This study aimed to investigate the effect of different feeding levels of Alfalfa pellet ration (APR) on the productive performance and economic feasibility of Pekin ducks (Anas platyrhynchos). A total of 270 one-day-old ducklings were used. The birds at seven-day-old were assigned to 9 indoor pens of (1×2.2m) with outdoor and swimming pool (1×9.8m) and Each box represented an indoor replicate with 30 ducklings. The feeding program for Pekin Duck group treatments with alfalfa pellet rations (47% alfalfa) was used as a replacement to the basal diet at different percentages (0%, 25%, and 50%) for control (T0), first (T1) and second (T2) groups. The results showed no significant differences among treatments except accumulative feed intake, feed conversion ratio, and mortality percentage, which showed significant differences among the treatments, the second treatment (50%) resulted in a higher accumulative feed intake, lower production index, and lower mortality% compared to the control and first treatment. The economic profit of the second treatment was the highest. The treatments showed a non-significant effect on carcass percentage except back and neck cuts. There were significant effects of sex on live body weight at marketing age and on the neck and breast cuts, male neck% were significantly higher than females, while females showed significantly higher breast%. In general, feeding ducks with a 25% of Alfalfa pellet ration improved production performance, while feeding ducks with a 50% Alfalfa pellet ration improved economic values.